2019
DOI: 10.1002/adsc.201900709
|View full text |Cite
|
Sign up to set email alerts
|

Toward Automated Enzymatic Glycan Synthesis in a Compartmented Flow Microreactor System

Abstract: Immobilized microfluidic enzyme reactors (IMER) are of particular interest for automation of enzyme cascade reactions. Within an IMER, substrates are converted by paralleled immobilized enzyme modules and intermediate products are transported for further conversion by subsequent enzyme modules. By optimizing substrate conversion in the spatially separated enzyme modules purification of intermediate products is not necessary, thus shortening process time and increasing space-time yields. The IMER enables the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Heinzler et al developed a cascade of immobilized microfluidic enzyme reactors where intermediate products are transported for further conversion in subsequent reactor modules under optimal conditions for the production of glycan [117]. Six different enzymes, namely galactokinase, UDP-sugar pyrophosphorylase, UDP-glucosedehydrogenase, NADH oxidase, β1,4-galactosyltransferase and glucuronosyltransferase, were immobilized on magnetic particles and loaded to each microreactor compartment at the best loading yield (g immobilized enzyme per L of settled beads).…”
Section: Engineering Aspectsmentioning
confidence: 99%
“…Heinzler et al developed a cascade of immobilized microfluidic enzyme reactors where intermediate products are transported for further conversion in subsequent reactor modules under optimal conditions for the production of glycan [117]. Six different enzymes, namely galactokinase, UDP-sugar pyrophosphorylase, UDP-glucosedehydrogenase, NADH oxidase, β1,4-galactosyltransferase and glucuronosyltransferase, were immobilized on magnetic particles and loaded to each microreactor compartment at the best loading yield (g immobilized enzyme per L of settled beads).…”
Section: Engineering Aspectsmentioning
confidence: 99%
“…Coating (for example by poly-l-lysine) to obtain stable nonpyrogenic MNP suspension [115] product homogeneity quality reduction by concentration gradients and hot spots in the reaction flask [25,51] enhanced quality due to homogeneous morphology, narrow size distribution [25,67,116] high within one bacteria strain but strain variation possible [52][53][54]95] reproducibility, production rate and scale-up capability significant batch to batch variations in size, morphology, and magnetic properties [25,111,[117][118][119], poor scaling up capability. A reported study from Lin et al showed a production rate of 4.73 g/h for microfluidic synthesis comparing to 1.4 g/h for conventional synthesis with the same conditions [89] continuous production, no batch-to-batch variation, high scale-up capability high at the defined environmental conditions [92], mg/(L • day) production rate [52], high scale-up capability, though challenging due to long term bacteriostatic growth conditions [38,40,46,78] clogging not applicable microchannel-wall blocking during nucleation or by agglomeration [77,104,[120][121][122] not applicable automation poor feasible/integratable [66,123,124] capability of online characterization not applicable for batch, though magnetic characterization of whole batches by magnetic particle spectroscopy is feasible parameter control and synthesis adjustment feasible during synthesis, control of magnetic parameters by magnetic particle spectroscopy [25,125] and NMR [126] cost low, common lab equipment expensive microreactor fabrication expensive specialized equipment…”
Section: Comparison Of Different Synthesesmentioning
confidence: 99%
“…A recent contribution by Elling, Franzreb et al on the development of a continuous flow system for biocatalyzed cascade reactions towards non-sulfated human natural killer cell-1 (HNK-1) glycan epitope (29, Figure 10) included the preparation of uridine diphosphate galactose (28) as an intermediate, however with a slightly different approach [53] than Wang et al [52] Here, the preparation of 28 from 27 relied on the direct use of UTP and UDP-sugar pyrophosphorylase (USP). The entire process sequence relied on six enzymes immobilized on magnetic parti- Figure 8.…”
Section: Enzymatic Phosphorylationsmentioning
confidence: 99%
“…Chemical structure of the non-sulfated human natural killer cell-1 (HNK-1) glycan epitope. [53] Other specific applications involving flow dephosphorylation reactions were also reported. For instance, Wang et al de-scribed the use of a three-enzyme cascade featuring a capillary monolithic reactor for the degradation of DNA strands into single nucleosides.…”
Section: Enzymatic Phosphorylationsmentioning
confidence: 99%